How Can Zakat Drive Consumption Levels in Society? - Khusnul Lailia; Rina Rosia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to examine the role of zakat as an economic instrument that can encourage household consumption, increase income equality, and support macroeconomic stability within the framework of Islamic economics. As a form of wealth redistribution, zakat has an important function in distributing part of the muzakki's wealth to the mustahiq, thereby strengthening the purchasing power of low-income groups who tend to have higher marginal consumption. This increase in consumption then contributes to aggregate demand growth and expands economic activity. In addition, zakat acts as an automatic stabilizer that maintains the consumption capacity of vulnerable communities during economic slowdowns, thereby reducing the risk of a decline in aggregate demand and maintaining overall economic stability. This study uses a qualitative method with a literature review approach to examine various scientific sources related to zakat, consumption theory, and the concept of income distribution. The findings of the analysis show that the success of zakat as an economic instrument is greatly influenced by professional and transparent governance, as well as targeted distribution, particularly through productive zakat programs that encourage the independence of mustahiq. Zakat also has significant potential in strengthening the Islamic economic structure oriented towards justice through reducing inequality and improving community welfare. Thus, optimizing zakat management is a strategic effort to build an inclusive, sustainable economy that supports the empowerment of vulnerable groups.